(2a+2)(3-1)+7=31

Simple and best practice solution for (2a+2)(3-1)+7=31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2a+2)(3-1)+7=31 equation:


Simplifying
(2a + 2)(3 + -1) + 7 = 31

Reorder the terms:
(2 + 2a)(3 + -1) + 7 = 31

Combine like terms: 3 + -1 = 2
(2 + 2a)(2) + 7 = 31

Reorder the terms for easier multiplication:
2(2 + 2a) + 7 = 31
(2 * 2 + 2a * 2) + 7 = 31
(4 + 4a) + 7 = 31

Reorder the terms:
4 + 7 + 4a = 31

Combine like terms: 4 + 7 = 11
11 + 4a = 31

Solving
11 + 4a = 31

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 4a = 31 + -11

Combine like terms: 11 + -11 = 0
0 + 4a = 31 + -11
4a = 31 + -11

Combine like terms: 31 + -11 = 20
4a = 20

Divide each side by '4'.
a = 5

Simplifying
a = 5

See similar equations:

| 5(x-3)+7x=45 | | 23=6+.25(8-12x) | | 12=-3b+3 | | 8-4x=72 | | 3(x-4)+2x-7(x-5)=-1 | | 6+.5(x-2)=9 | | 1(x+4)+x-4(x-4)=x+8 | | -5x-3=-48 | | 3n-9=51 | | t+18.=23.9 | | 3x+6=-42 | | 2y+7y=15 | | 4x-4=(x+2) | | x-18=87 | | 5x+6-x^2+4=4x+2 | | 2z-19=5z+2 | | 6m+15=8m-3 | | 5x+6-x^2+10=4x+2 | | 4m+22=7m-2 | | |2/3x+2/3|=2/3 | | 4x^2-21x+35=3x+8 | | 8(t-3)+4+=6(2t+1)-10 | | 0.6x-1.5=1 | | 6x^2-15x=9 | | -2x-6(-x-6)=-4 | | -8-b=6 | | 5x-3(-6x+14)=119 | | 3xy-4-6x+2y=0 | | 3x+5x=9x-8 | | 4x+4(-4x-17)=-164 | | 2a+9b= | | 6x+7(2x-6)=-182 |

Equations solver categories